2018
DOI: 10.1093/mnras/sty2652
|View full text |Cite
|
Sign up to set email alerts
|

3D Aeronomy modelling of close-in exoplanets

Abstract: We present a 3D fully self-consistent multi-fluid hydrodynamic aeronomy model to study the structure of a hydrogen dominated expanding upper atmosphere around the hot Jupiter HD 209458b and the warm Neptune GJ 436b. In comparison to previous studies with 1D and 2D models, the present work finds such 3D features as zonal flows in upper atmosphere reaching up to 1 km/s, the tilting of the planetary outflow by Coriolis force by up to 45 degrees and its compression around equatorial plane by tidal forces. We also … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 42 publications
5
49
0
Order By: Relevance
“…The revealed influence of the helium abundance on the HI, OI and MgII absorption (see also Shaikhislamov et al 2018b) and the obtained constrains in that respect, may be of interest regarding the recent observations in He lines (Oklopčić et al 2018). In particular, it has been shown that the absorption in all considered lines decreases at He abundancies above 0.1 due to the decrease of atmospheric height scale and the related steeper decrease of the density with the height.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The revealed influence of the helium abundance on the HI, OI and MgII absorption (see also Shaikhislamov et al 2018b) and the obtained constrains in that respect, may be of interest regarding the recent observations in He lines (Oklopčić et al 2018). In particular, it has been shown that the absorption in all considered lines decreases at He abundancies above 0.1 due to the decrease of atmospheric height scale and the related steeper decrease of the density with the height.…”
Section: Discussionmentioning
confidence: 68%
“…Since the cross-section of He photo-ionization at Eph >24.6 eV is an order of magnitude higher than that of the HI photo-ionization, this effect is not small. Second, even at relatively low abundancy ~3% helium significantly increases, due to its photoionization, the density of electrons in the upper atmosphere below the thermosphere maximum (Shaikhislamov et al 2018b). Therefore, the photoelectrons would lose their energy via Coulomb collisions more rapidly.…”
Section: The Numerical Model and Absorption Parametersmentioning
confidence: 99%
“…This indicates a presence of a massive hydrogen cloud around this planet, which obscures almost half of the emission in the stellar Lyα line (the absorption during a transit is ≈56%). Numerical modeling confirms that GJ 436b is surrounded by a big cloud of atomic hydrogen with a complex structure (Bourrier et al , 2016Loyd et al 2017;Shaikhislamov et al 2018).…”
Section: Model Descriptionmentioning
confidence: 90%
“…fore, atomic hydrogen is the main atmospheric component thorough most of our simulation domain for the lower atmosphere (Shaikhislamov et al 2018). Some works (Hu et al 2015) have shown that planets like GJ 436b might accumulate a significant amount of helium due to faster atmospheric escape of hydrogen.…”
Section: Model Validation Gj 436bmentioning
confidence: 98%
“…Fully hydrodynamic models of planetary upper atmospheres have so far only been applied to H and He dominated atmospheres (e.g., Khodachenko et al 2015;Owen & Mohanty 2016;Shaikhislamov et al 2018) and to an atomic H and O gas by Guo (2019). In this letter, we study for the first time the hydrodynamic outflow of an atmosphere composed of heavier molecules orbiting a very active star.…”
Section: Introductionmentioning
confidence: 99%